Bacteriostatic deodorizing fabric and preparation process thereof

By loading amino amino -based salt in textile fabrics and using granules and mixed melting spinning wires, the existing antibacterial deodorization textile preparation process is complex and cost -high, and the long -acting bacteriostatic odor and odor of the fabrics and the smell of the fabric Good mechanical performance.

CN119332364AActive Publication Date: 2025-01-21LUOLAI LIFESTYLE TECH CO LTD +1

Patent Information

Application Number
CN202411607398.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-21
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The existing antibacterial deodorization textile preparation process is complex, has high cost and has a negative impact on the mechanical properties of the fabric. It is not clear whether it has long-term deodorization properties.

Method used

The amino -based salt load is used to prepare the odor on the porous carrier, and the textile fabrics with long -acting antibacterial deodorization performance are prepared through step -making, mixed melting spinning, and thermal treatment steps.

Benefits of technology

The simplification and cost of preparation technology have been achieved. The fabric has good mechanical properties and long -term bacteriostatic and odor performance, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129971630000121
    Figure BDA0005129971630000121
  • Figure BDA0005129971630000122
    Figure BDA0005129971630000122
  • Figure BDA0005129971630000131
    Figure BDA0005129971630000131
Patent Text Reader

Abstract

The invention belongs to the technical field of functional fibers, and provides a bacteriostatic and deodorant fabric and a preparation process thereof, the process comprises the following steps: loading aminoguanidine salt onto a porous carrier to prepare a deodorant; a deodorant, a lubricant, a dispersant, an antibacterial agent and a matrix are used as raw materials, granulation is performed, and functional master batches are prepared; blending, melting and spinning the functional master batch and polypropylene slices to obtain composite fibers; the composite fibers are subjected to heat treatment in a loose state and then blended with cotton fibers or viscose fibers, and the antibacterial and deodorant fabric is obtained. The preparation process is simple, easy to regulate and control, low in energy consumption and low in cost, and the prepared fabric has long-acting bacteriostasis and deodorization performance and is good in mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of functional fibers, and in particular to an antibacterial and deodorizing fabric and a preparation process thereof. Background Art

[0002] Textiles are essential functional products for human life. Due to their microporous structure, they are very easy to absorb and contaminate microorganisms. In addition, the appropriate temperature and humidity on the human body surface, the secreted oil and sweat, etc., create favorable conditions for the reproduction and growth of microorganisms under certain special circumstances. These bacteria and other pathogenic microorganisms not only cause harm to the human body, but also decompose human secretions to produce odor.

[0003] With the rapid development of modern textile science and technology and the increasing demand for functionality and comfort of textiles, textiles with antibacterial and deodorizing effects are often more popular with consumers.

[0004] In order to eliminate odors such as sweat, body odor, excrement, smoke, and old age from the human body and the air, researchers have developed a variety of deodorizing fibers that remove odors through ion exchange, chemical reaction, physical adsorption, and odor masking.

[0005] For example, the patent application document with publication number CN118166445A discloses an antibacterial and deodorizing coffee carbon fiber fabric and a preparation method thereof, wherein coffee grounds are first carbonized and then oxidized, and then loaded with phytic acid to obtain modified oxidized coffee carbon; 1,3 diaminoguanidine hydrochloride and 1,4 diamino 2-butene are reacted to obtain guanidine oligomers; guanidine oligomers are reacted with 2(4-nitrophenyl) dimethyl malonate to obtain polyamide; 2,4 dihydroxybenzophenone is reacted with 3-chloro-1-propanethiol to obtain 2-hydroxy-4(3-mercaptopropoxy)benzophenone; polyamide is reacted with 2-hydroxy-4(3-mercaptopropoxy)benzophenone and hydrogen in sequence to obtain modified polyamide; modified polyamide and modified oxidized coffee carbon are prepared into fiber spinning solution, and antibacterial and deodorizing coffee carbon fiber is obtained by electrostatic spinning; and then woven into antibacterial and deodorizing coffee carbon fiber fabric.

[0006] For another example, the patent with publication number CN113784786B discloses a method for manufacturing a deodorant-containing processing fluid and a deodorant product using the same. The method points out that hydrazine compounds such as adipic acid dihydrazide, carbohydrazide, succinic acid dihydrazide, oxalic acid dihydrazide, and aminoguanidine salts such as aminoguanidine hydrochloride, aminoguanidine sulfate, and aminoguanidine bicarbonate can be used as deodorants for aldehyde gases to remove odorous gases such as formaldehyde, acetaldehyde, and nonenal.

[0007] However, the above methods either have complicated preparation processes and high costs, or do not clearly define the effects of deodorants on the mechanical properties of textile fabrics, and do not clearly define whether they have long-lasting deodorizing properties.

[0008] Based on this, a simpler and easier-to-control preparation method is needed to prepare textile fabrics with long-lasting antibacterial and deodorizing properties to facilitate industrial production. Summary of the invention

[0009] In view of the above-mentioned shortcomings of the prior art, the present invention provides an antibacterial and deodorizing fabric and a preparation process thereof to solve the problems that the preparation process of the existing antibacterial and deodorizing textiles is complicated and has a certain negative impact on the mechanical properties of the fabric.

[0010] To achieve the above and related purposes, the present invention adopts the following technical solutions:

[0011] The first aspect of the present invention provides a preparation process of an antibacterial and deodorizing fabric, comprising the following steps:

[0012] (1) loading an aminoguanidine salt onto a porous carrier to prepare a deodorant;

[0013] (2) Using a deodorant, a lubricant, a dispersant, an antibacterial agent and a matrix as raw materials, granulating to prepare a functional masterbatch;

[0014] (3) blending the functional masterbatch and the polypropylene chips for melt spinning to obtain composite fibers, wherein the functional masterbatch and the polypropylene chips are blended in a mass ratio of (0.5-5): (95-99.5);

[0015] (4) The composite fiber is heat-treated in a relaxed state and then blended with cotton fiber or viscose fiber to obtain an antibacterial and deodorizing fabric.

[0016] In one embodiment of the present application, in step (1), the aminoguanidine salt is aminoguanidine sulfate, aminoguanidine nitrate or aminoguanidine hydrochloride.

[0017] In one embodiment of the present application, the porous carrier is activated carbon and / or sepiolite.

[0018] In one embodiment of the present application, step (1) further includes: dissolving aminoguanidine salt in water, preparing an impregnation solution, and impregnating the porous carrier in the impregnation solution to obtain a deodorant, wherein the loading rate of the porous carrier is 15-30%.

[0019] In one embodiment of the present application, in step (2), the lubricant includes one or more of calcium stearate, oleic acid, fatty acid amide, silicone oil, polyester, and carboxylic acid;

[0020] and / or, the dispersant includes one or more of hexenyl bisstearamide, stearic acid monoglyceride, tristearic acid glyceride, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, copper stearate, ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer, and polyethylene wax;

[0021] and / or, the substrate comprises one or more of polyethylene, polypropylene, polyvinyl chloride, polyamide, polyester, polyurethane;

[0022] And / or, the antibacterial agent includes one or more of nano titanium dioxide, nano zinc oxide, and nano cerium oxide.

[0023] In one embodiment of the present application, step (2) further comprises: blending and drying the deodorant, lubricant, dispersant, antibacterial agent and matrix, and melting, extruding, cooling, drawing, pelletizing and drying by screw extrusion to obtain a functional masterbatch, wherein:

[0024] The mass ratio of the deodorant, lubricant, dispersant, antibacterial agent and base is (20-30): (0.5-3): (0.5-3): (1-2): (62-78).

[0025] In one embodiment of the present application, in step (3), the spinning temperature of the melt spinning is 130-150°C.

[0026] In one embodiment of the present application, in step (4), the heat treatment temperature is 95-100° C.;

[0027] And / or, the heat treatment time is 15 to 20 minutes.

[0028] In one embodiment of the present application, after the composite fiber is heat-treated in a relaxed state, the blending ratio of the composite fiber with the cotton fiber or the viscose fiber is (35-50):(50-65).

[0029] A second aspect of the present invention provides an antibacterial and deodorizing fabric, which is prepared according to the above-mentioned preparation process.

[0030] The beneficial technical effects of the present invention are:

[0031] The preparation process of the invention is simple, easy to control, low in energy consumption and low in cost; the prepared fabric has long-lasting antibacterial and deodorizing properties and good mechanical properties.

[0032] The present invention uses aminoguanidine salt as a deodorant for aldehyde gases such as 2-nonenal, and uses a porous carrier as a deodorant for odors such as ammonia, acetic acid, and isovaleric acid, and the aminoguanidine salt is loaded onto the porous carrier by an impregnation method to prepare a deodorant. The aminoguanidine salt of the present invention can perform rapid one-way chemical adsorption on aldehyde gases at room temperature, and undergo a dehydration reaction with the aldehyde gases, thereby achieving the purpose of deodorization, and the byproducts generated by the reaction, such as methyleneamino compounds, are easily volatile and are then adsorbed by the porous carrier, without having a negative impact on the human body.

[0033] The temperature of melt spinning of polypropylene fiber is usually 180±50°C, which is higher than the melting point of aminoguanidine salt. If the deodorant is directly blended with polypropylene chips for melt spinning, the aminoguanidine salt will melt and lose its deodorizing effect. Therefore, the present invention uses lubricants to prepare functional masterbatches with cooling effect, reduce the temperature of melt spinning, and control the amount of lubricants. The spinning temperature can be reduced by 20 to 30°C, which is lower than the melting point of aminoguanidine salt, thereby ensuring that the aminoguanidine salt on the final fiber is not ineffective. At the same time, the present invention uses dispersants to avoid the adhesion of functional masterbatches, so that the functional masterbatches are evenly dispersed in polypropylene chips.

[0034] In addition, the present invention controls the blending ratio of melt spinning to ensure that the final fabric has good mechanical properties. The present invention also controls the blending ratio so that the prepared fabric can be better applied to household textiles.

[0035] The present invention also heat treats the composite fiber to promote fiber splitting and make the internal structure of the fiber relatively fluffy, so as to further improve the air permeability of the fabric, thereby promoting air circulation, reducing the humidity on the surface of the fabric, and reducing the possibility of bacterial growth. In addition, the present invention avoids the negative impact of fabric pilling by controlling the heat treatment temperature and time.

[0036] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. DETAILED DESCRIPTION

[0037] Unless otherwise defined, all technical and / or scientific terms used herein have the same meaning as the general understanding of a person of ordinary skill in the art to which the present invention belongs. It should be understood that certain features of the present invention (described in the context of separate embodiments for clarity) may also be provided in combination in a single embodiment. On the contrary, multiple features of the present invention (described in the context of a single embodiment for brevity) may also be provided separately or in any suitable combination or in any other described embodiment of the present invention when appropriate. Certain features described in the context of various embodiments will not be considered as essential features of those embodiments unless the embodiment is inoperable without those elements. The present invention is further described below by specific specific examples, but it should be noted that the specific process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention, and the protection scope of the present invention cannot be limited thereto. All equivalent changes or modifications made according to the spirit and essence of the present invention should be included in the protection scope of the present invention.

[0038] The present invention discloses a process for preparing an antibacterial and deodorizing fabric, comprising the following steps:

[0039] (1) An aminoguanidine salt is dissolved in water to prepare an impregnation solution, and a porous carrier is impregnated in the impregnation solution to obtain a deodorant, wherein the loading rate of the porous carrier is 15 to 30%.

[0040] In this step, the aminoguanidine salt is aminoguanidine sulfate, aminoguanidine nitrate or aminoguanidine hydrochloride;

[0041] In this step, parameters such as the concentration of the impregnation liquid, the impregnation ratio, the impregnation temperature, the number of impregnations, etc. are conventionally adjusted according to the load rate requirements and are not specifically limited here.

[0042] (2) The deodorant, lubricant, dispersant, antibacterial agent and matrix are blended and dried, and then melted, extruded, cooled, drawn, pelletized and dried by screw extrusion to obtain a functional masterbatch, wherein the mass ratio of the deodorant, lubricant, dispersant, antibacterial agent and matrix is ​​(20-30): (0.5-3): (0.5-3): (1-2): (62-78).

[0043] In this step, the lubricant includes one or more of calcium stearate, oleic acid, fatty acid amide, silicone oil, polyester, and carboxylic acid;

[0044] In this step, the dispersant includes one or more of hexenyl bisstearamide, stearic acid monoglyceride, tristearic acid glyceride, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, copper stearate, ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer, and polyethylene wax;

[0045] In this step, the substrate includes one or more of polyethylene, polypropylene, polyvinyl chloride, polyamide, polyester, and polyurethane;

[0046] In this step, the antibacterial agent includes one or more of nano titanium dioxide, nano zinc oxide, and nano cerium oxide.

[0047] (3) The functional masterbatch and the polypropylene chips are blended and melt-spun at a mass ratio of (0.5-5):(95-99.5) to obtain composite fibers.

[0048] In this step, the spinning temperature of melt spinning is 130-150°C;

[0049] In this step, the spinning speed is 400-600 m / min;

[0050] In this step, the drafting multiple is 3 to 4 times.

[0051] (4) The composite fiber is heat-treated in a relaxed state and then blended with cotton fiber or viscose fiber to obtain an antibacterial and deodorizing fabric.

[0052] In this step, the heat treatment temperature is 95-100°C;

[0053] In this step, the heat treatment time is 15 to 20 minutes.

[0054] In this step, after the composite fiber is heat-treated in a relaxed state, the composite fiber is blended with the cotton fiber or the viscose fiber in a blending ratio of (35-50):(50-65).

[0055] The present invention also provides an antibacterial and deodorizing fabric, which is prepared according to the above preparation process.

[0056] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0057] Example 1

[0058] (1) Aminoguanidine hydrochloride is dissolved in water to prepare an impregnation solution, and activated carbon is impregnated in the impregnation solution to obtain a deodorant, wherein the loading rate of the activated carbon is 15%.

[0059] (2) The deodorant, calcium stearate, hexenyl bisstearamide, nano titanium dioxide and polyethylene are blended and dried in a mass ratio of 20:0.5:0.5:2:77, and then melted, extruded, cooled, drawn, pelletized and dried by screw extrusion to obtain a functional masterbatch.

[0060] (3) The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 0.5:99.5 at a spinning temperature of 130° C., a spinning speed of 400 m / min, and a drafting multiple of 3 times to obtain a composite fiber.

[0061] (4) The composite fiber is heat treated in a relaxed state at a temperature of 95° C. for 15 min.

[0062] (5) The heat-treated composite fiber is blended with cotton fiber at a blending ratio of 35:65 to obtain an antibacterial and deodorizing fabric.

[0063] Example 2

[0064] The difference between this embodiment and embodiment 1 is that:

[0065] The loading rate of activated carbon was 20%.

[0066] Example 3

[0067] The difference between this embodiment and embodiment 1 is that:

[0068] The loading rate of activated carbon was 25%.

[0069] Example 4

[0070] The difference between this embodiment and embodiment 1 is that:

[0071] The loading rate of activated carbon was 30%.

[0072] Example 5

[0073] The difference between this embodiment and embodiment 1 is that:

[0074] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 1:99 to obtain composite fibers.

[0075] Example 6

[0076] The difference between this embodiment and embodiment 1 is that:

[0077] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 2:98 to obtain composite fibers.

[0078] Example 7

[0079] The difference between this embodiment and embodiment 1 is that:

[0080] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 3:97 to obtain composite fibers.

[0081] Example 8

[0082] The difference between this embodiment and embodiment 1 is that:

[0083] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 3.5:96.5 to obtain composite fibers.

[0084] Example 9

[0085] The difference between this embodiment and embodiment 1 is that:

[0086] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 4:95 to obtain composite fibers.

[0087] Example 10

[0088] The difference between this embodiment and embodiment 1 is that:

[0089] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 4.5:95 to obtain composite fibers.

[0090] Embodiment 11

[0091] The difference between this embodiment and embodiment 1 is that:

[0092] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 5:99 to obtain composite fibers.

[0093] Example 12

[0094] The difference between this embodiment and embodiment 1 is that:

[0095] The spinning temperature of the melt spinning was 135°C.

[0096] Example 13

[0097] The difference between this embodiment and embodiment 1 is that:

[0098] The spinning temperature of the melt spinning was 140°C.

[0099] Embodiment 14

[0100] The difference between this embodiment and embodiment 1 is that:

[0101] The spinning temperature of the melt spinning was 145°C.

[0102] Embodiment 15

[0103] The difference between this embodiment and embodiment 1 is that:

[0104] The spinning temperature of the melt spinning was 150°C.

[0105] Example 16

[0106] The difference between this embodiment and embodiment 1 is that:

[0107] Aminoguanidine hydrochloride is dissolved in water to prepare an impregnation solution, and activated carbon and sepiolite (the mass ratio of activated carbon to sepiolite is 1:1) are impregnated in the impregnation solution to obtain a deodorant, wherein the loading rate of activated carbon is 15%.

[0108] Comparative Example 1

[0109] The difference between this comparative example and Example 1 is:

[0110] The loading rate of activated carbon was 10%.

[0111] Comparative Example 2

[0112] The difference between this comparative example and Example 1 is:

[0113] The loading rate of activated carbon was 35%.

[0114] Comparative Example 3

[0115] The difference between this comparative example and Example 1 is:

[0116] The functional masterbatch and polypropylene chips were blended and melt-spun at a mass ratio of 10:90 to obtain composite fibers.

[0117] Comparative Example 4

[0118] The difference between this comparative example and Example 1 is:

[0119] (3) The deodorant, hexenyl bisstearamide, nano titanium dioxide and polyethylene are blended and dried in a mass ratio of 20:0.5:2:77.5, and then melted, extruded, cooled, drawn, pelletized and dried by screw extrusion to obtain a functional masterbatch.

[0120] (4) The functional masterbatch and the polypropylene chips were blended and melt-spun at a mass ratio of 0.5:99.5 at a spinning temperature of 180° C., a spinning speed of 400 m / min, and a drafting multiple of 3 times to obtain a composite fiber.

[0121] Comparative Example 5

[0122] The difference between this comparative example and Example 1 is:

[0123] The composite fibers were not heat treated.

[0124] Comparative Example 6

[0125] The difference between this comparative example and Example 1 is:

[0126] Use activated carbon as a deodorant.

[0127] Performance Testing

[0128] Antibacterial property: According to GB / T 20944.3-2008 “Evaluation of antibacterial properties of textiles Part 3 Oscillation method”, the antibacterial properties of the fabrics before and after treatment against Staphylococcus aureus ATCC6538, Escherichia coli ATCC 25922 and Candida albicans ATCC10231 were determined by the oscillation flask method.

[0129] The antibacterial and deodorizing fabrics of Examples 1 to 16 and Comparative Examples 1 to 6 were tested for antibacterial properties, and the results were recorded as the initial antibacterial rate; then, the antibacterial and deodorizing fabrics prepared in the examples and the fabrics prepared in the comparative examples were washed according to the following method: at 25°C, the antibacterial and deodorizing fabrics prepared in the examples and the fabrics prepared in the comparative examples were soaked in a 20% sodium stearate solution for 5 minutes, then washed 5 times with clean water, dried, and one wash was completed. The antibacterial and deodorizing fabrics prepared in the examples and the fabrics prepared in the comparative examples were washed 10 times and 20 times, respectively. The antibacterial test results are shown in Tables 1 and 2.

[0130] Dissolution of antimicrobial substances: The dissolution test method of antimicrobial substances in Appendix A of GB / T 31713-2015 is used for testing. The specific testing method is as follows:

[0131] Examples 1 to 16 were woven into antibacterial and deodorizing fabrics with specifications of 40s*40s / 144*85, and 1.5cm*1.5cm fabric samples were cut from different parts of the fabrics of each example as test samples, three pieces each;

[0132] Comparative Examples 1 to 6 were woven into fabrics with specifications of 40s*40s / 144*85, and 1.5cm*1.5cm fabric samples were cut from different parts of the comparative example fabrics as samples to be tested, three pieces each;

[0133] Three pieces of two-layer 100% polyester knitted fabrics sewn together were used as wash fabrics, the mass per unit area of ​​which was 125% of the mass per unit area of ​​the sample to be tested, and the size of each wash fabric was 30 cm*30 cm.

[0134] Wash the above-mentioned samples to be tested, the samples to be tested and the accompanying fabrics once according to the requirements of Appendix B and Appendix C of FZ / T 73023-2006 and set aside for use;

[0135] Prepare several standard blank samples according to Appendix A of FZ / T 73023-2006, cut them into 1.5cm*1.5cm, wash them once according to Appendix B of FZ / T 73023-2006, and set aside;

[0136] Sterilize the washed standard blank samples, the samples to be tested, and the samples to be tested at 103 kPa and 121° C. for 15 min for later use;

[0137] Staphylococcus aureus (ATCC 6538), Escherichia coli (ATCC 25922), and Candida albicans (ATCC10231) were selected as test strains, and multiple groups of antibacterial substance dissolution tests were performed on the above sterilized standard blank samples, each test sample, and each test sample. The antibacterial substance dissolution of each test sample and each test sample was determined based on the maximum inhibition zone width (D) of each test sample and each test sample against Staphylococcus aureus, Escherichia coli, and Candida albicans. The test results are shown in Table 3.

[0138] Deodorizing performance of textiles: According to GB / T 33610.3-2019 "Determination of Deodorizing Performance of Textiles", the deodorizing performance of the antibacterial and deodorizing fabrics prepared in Examples 1 to 16 and the fabrics prepared in Comparative Examples 1 to 6 were tested, as follows:

[0139] The reagents include: ammonia, acetic acid sample gas, isovaleric acid (purity 98.0%), 2-nonenal (purity 95.0%), diluent gas (nitrogen with a purity of 99.99% or above), and ethanol (analytical grade).

[0140] The size is (50±2.5)cm 2 Four pieces of the antibacterial and deodorizing fabrics of Examples 1 to 16 and four pieces of the fabrics of Comparative Examples 1 to 6 were used as test samples.

[0141] Gas chromatography: prepare several 500 mL glass conical flasks, half of which are used for sample testing and the other half for blank testing. Each example and comparative example is tested separately for isovaleric acid and 2-nonenal.

[0142] Before the test, the conical flask was purged with nitrogen gas with a volume greater than 5 times the volume of the conical flask, and the humidity and test environment were adjusted.

[0143] Accurately weigh 20 g of isovaleric acid in a volumetric flask and dilute to the mark with ethanol; accurately weigh 10 g of 2-nonenal in a volumetric flask and dilute to the mark with ethanol.

[0144] The above-mentioned samples to be tested are used for isovaleric acid and 2-nonenal testing respectively. Each sample to be tested is laid flat on the bottom of a conical flask, 1000mL of nitrogen is blown into the conical flask to exclude the air inside, and the bottle mouth is sealed with a sealing film. Use a syringe to take 5μL of the above-prepared isovaleric acid and 2-nonenal solutions, and inject them along the inner wall of the conical flask through the sealing film. The above solutions should not contact the samples to be tested. Seal the pinholes with a sealing film on the original sealing film.

[0145] Leave it to stand for 2 hours in the standard atmospheric environment specified in GB / T 6529.

[0146] Repeat the above steps for blank test without adding the sample to be tested.

[0147] After 2 hours of contact, hold the conical bottle mouth and shake the conical bottle containing or not containing the sample to be tested vigorously for about 20 times within 20 seconds. Insert the gas-tight injection needle vertically about 4 cm into the center of the sealing film at the conical bottle mouth. Use the gas-tight injection needle to extract the gas to be tested in the bottle, and determine the sampling amount of the gas to be tested according to the type of gas chromatograph used.

[0148] Detection tube method: Place each sample to be tested in a sampling bag, evacuate the gas in the sampling bag with an aspirator or vacuum pump, inject 3L of ammonia and acetic acid sample gas into the sampling bag with an air pump, let it stand for 2 hours, use a 100mL syringe to draw 100mL of the gas to be tested from the sampling bag containing the sample, and read the color change position scale through the detection tube.

[0149] The odor chemical component concentration reduction rate (ORR%) was calculated, and the calculation results are shown in Table 4.

[0150] Mechanical properties: The wear resistance and elongation at break of the antibacterial and deodorizing fabrics of Examples 1 to 16 and Comparative Examples 1 to 6 were tested. The test results are shown in Table 5.

[0151] The experimental data and their analysis are as follows:

[0152] Table 1 Antibacterial test results of fabrics of various embodiments and comparative examples

[0153]

[0154] Table 2 Antibacterial test results of fabrics of each embodiment and each comparative example

[0155]

[0156]

[0157] (Note: The antibacterial rate against Staphylococcus aureus and Escherichia coli is ≥70%, and the antibacterial rate against Candida albicans is ≥60%. The sample has antibacterial effect)

[0158] It can be seen from Table 1 and Table 2 that after 20 washes, the antibacterial and deodorizing fabrics of Examples 1 to 16 of the present invention have an antibacterial rate of >95% against Staphylococcus aureus, Escherichia coli and Candida albicans, which indicates that the antibacterial and deodorizing fabrics of the present invention have long-lasting antibacterial properties and good water washability.

[0159] From the data of Examples 1 to 4 and Comparative Examples 1 to 2, it can be seen that the antibacterial rate first increases and then decreases to a stable level as the loading rate increases. Considering the cost and efficiency, the loading rate of the present invention is preferably 25%.

[0160] From the data of Examples 1, 5 to 11 and Comparative Example 3, it can be seen that the antibacterial rate increases with the increase in the amount of the blended functional masterbatch and tends to be stable. Under the premise of considering the cost, the present invention preferably blends the functional masterbatch and the polypropylene chips at a mass ratio of 3.5:96.5 for melt spinning.

[0161] From the data of Examples 1 and 12 to 15, it can be seen that the antibacterial rate increases with the increase of spinning temperature. When the spinning temperature reaches 180°C in Comparative Example 4, the functional masterbatch has no cooling effect. During the spinning process, aminoguanidine hydrochloride fails, resulting in a decrease in the antibacterial rate of the final fabric.

[0162] The fabric prepared in Comparative Example 5 is not heat-treated, has no fluffy structure inside, and has poor air permeability, which can provide a favorable environment for the growth of microorganisms, and thus has a low antibacterial rate.

[0163] The fabric prepared in Comparative Example 6 did not add aminoguanidine hydrochloride, and its inhibitory effect on Escherichia coli and Staphylococcus aureus was significantly reduced, and the antibacterial property was poor.

[0164] Table 3 Dissolution Test of Antibacterial Substances in Fabrics of Each Example and Comparative Examples 1 - 3

[0165]

[0166]

[0167] (Note: Width of the inhibition zone D: D ≤ 1 mm indicates non - dissolution, 1 mm < D ≤ 5 mm indicates slight dissolution, 5 mm < D ≤ 10 mm indicates moderate dissolution, and D > 10 mm indicates dissolution)

[0168] As can be seen from Table 3, the maximum inhibition zone width of the antibacterial and deodorizing fabric prepared by the present invention is all < 1.1 mm, and the dissolution of antibacterial substances shows non - dissolution and good slight dissolution. This indicates that the antibacterial and deodorizing fabric of the present invention will not cause harm to human health and is safer and more reliable. Although the dissolution of antibacterial substances in the fabrics of Comparative Examples 4 - 6 shows slight dissolution, their maximum inhibition zone width is significantly higher than that of the antibacterial and deodorizing fabric of the present invention, and their safety is lower than that of the antibacterial and deodorizing fabric of the present invention.

[0169] Table 4 Deodorizing Performance of Fabrics of Each Example and Each Comparative Example

[0170]

[0171]

[0172] As can be seen from Table 4, under the combined action of antibacterial agent, activated carbon and aminoguanidine salt, the antibacterial and deodorizing fabric prepared by the present invention has excellent deodorizing effects on ammonia, acetic acid, isovaleric acid and 2 - nonenal odor molecules. The deodorizing property of the antibacterial and deodorizing fabric of the present invention is higher than that of the comparative fabric. Moreover, under the condition of too high spinning temperature, the deodorizing rate of the fabric of Comparative Example 4 for 2 - nonenal drops significantly. The fabric of Comparative Example 6 does not contain aminoguanidine salt which has deodorizing effect on aldehyde gases, and only relies on activated carbon and low - content antibacterial agent for deodorization, so the deodorizing effect is poor.

[0173] The fabric of Comparative Example 5 has poor air permeability, and its deodorizing effect is inferior to that of the antibacterial and deodorizing fabric of the examples of the present invention.

[0174] Table 5 Mechanical Properties of Fabrics of Each Example and Each Comparative Example

[0175]

[0176]

[0177] (The elongation at break of polypropylene fabric without any treatment is 25%, and the abrasion resistance of pure cotton fabric > 200 times)

[0178] As shown in Table 5, the antibacterial and deodorizing fabrics of Examples 1 to 16 of the present invention have excellent mechanical properties, which are close to the mechanical properties of untreated polypropylene fabrics, and there is no obvious decrease in mechanical properties. Compared with pure cotton fabrics, they are more wear-resistant and more durable.

[0179] From the data of Examples 1 to 16 and Comparative Examples 1 to 6, it can be seen that the loading rate of aminoguanidine salt on activated carbon is too high, the blending ratio of functional masterbatch is too high, and the spinning temperature is too high, all of which affect the mechanical properties of the fabric, causing the elongation at break of the fabric to decrease significantly, with the maximum elongation at break decreasing by 32%; and the wear resistance is relatively reduced.

[0180] In addition, it can be seen from the above data that the loading rate of the aminoguanidine salt of the present invention on the activated carbon is preferably 25%, and the blending ratio of the functional masterbatch and the polypropylene chips is preferably 3.5:96.5.

[0181] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A preparation process of antibacterial and deodorizing fabric, characterized in that: The following steps are involved: (1) loading an aminoguanidine salt onto a porous carrier to prepare a deodorant; (2) Using a deodorant, a lubricant, a dispersant, an antibacterial agent and a matrix as raw materials, granulating to prepare a functional masterbatch; (3) blending the functional masterbatch and the polypropylene chips for melt spinning to obtain composite fibers, wherein the functional masterbatch and the polypropylene chips are blended in a mass ratio of (0.5-5): (95-99.5); (4) The composite fiber is heat-treated in a relaxed state and then blended with cotton fiber or viscose fiber to obtain an antibacterial and deodorizing fabric.

2. The preparation process according to claim 1, characterized in that: In the step (1), the aminoguanidine salt is aminoguanidine sulfate, aminoguanidine nitrate or aminoguanidine hydrochloride.

3. The preparation process according to claim 1, characterized in that: In the step (1), the porous carrier is activated carbon and / or sepiolite.

4. The preparation process according to claim 1, characterized in that: The step (1) further comprises: dissolving the aminoguanidine salt in water to prepare an impregnation solution, and impregnating the porous carrier in the impregnation solution to obtain the deodorant, wherein the loading rate of the porous carrier is 15-30%.

5. The preparation process according to claim 1, characterized in that: In the step (2), the lubricant includes one or more of calcium stearate, oleic acid, fatty acid amide, silicone oil, polyester, and carboxylic acid; and / or, the dispersant includes one or more of hexenyl bisstearamide, stearic acid monoglyceride, tristearic acid glyceride, barium stearate, zinc stearate, calcium stearate, cadmium stearate, magnesium stearate, copper stearate, ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer, and polyethylene wax; and / or, the substrate comprises one or more of polyethylene, polypropylene, polyvinyl chloride, polyamide, polyester, polyurethane; And / or, the antibacterial agent includes one or more of nano titanium dioxide, nano zinc oxide, and nano cerium oxide.

6. The preparation process according to claim 1, characterized in that: The step (2) further comprises: blending and drying the deodorant, lubricant, dispersant, antibacterial agent and matrix, and melting, extruding, cooling, drawing, pelletizing and drying through screw extrusion to obtain the functional masterbatch, wherein: The mass ratio of the deodorant, the lubricant, the dispersant, the antibacterial agent and the matrix is ​​(20-30): (0.5-3): (0.5-3): (1-2): (62-78).

7. The preparation process according to claim 1, characterized in that: In the step (3), the spinning temperature of melt spinning is 130-150°C.

8. The preparation process according to claim 1, characterized in that: In the step (4), the heat treatment temperature is 95 to 100° C.; And / or, the heat treatment time is 15 to 20 minutes.

9. The preparation process according to claim 1, characterized in that: After the composite fiber is heat-treated in a relaxed state, the blending ratio of the composite fiber with the cotton fiber or the viscose fiber is (35-50): (50-65).

10. An antibacterial and deodorizing fabric, characterized in that: The fabric is prepared according to the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for manufacturing deodorizing processing fluids containing deodorants and deodorizing products using the same.

    CN113784786B

  • Bacteriostatic and deodorant coffee carbon fiber fabric and preparation method thereof

    CN118166445A

  • Composite deodorizing viscose fiber, fabric and preparation method of composite deodorizing viscose fiber

    CN118727176A

  • Method for preparing boron nitride continuous fiber through aldehyde-cyano guanidine-boron oxygen resin filamentation

    CN118910767A

  • Fibrous sheet, method for producing the same, deodorant, and air filter

    JP2008138300A

Cited By

  • High-strength composite antibacterial monofilament and preparation method thereof

    CN121629563A